Strategi Komunikasi Bisnis di Saung Angklung Udjo - Kusumawaty, Wulandari (UPT Publikasi Ilmiah UNISBA, 2023)
Abstract. Research Business Communication Strategy Saung Angklung Udjo raises the uniqueness of business communication by maintaining the culture that is owned by Sundanese culture. The culture that is the basis of business communication is derived from a love of Sundanese culture, experience in producing quality work, regeneration, preparation of communication planning based on Google trends analysis, planning of short-term communication focused on optimizing information content and using web conversion, while long-term focus on building communication with external parties. The internal communication strategy focuses on creativity and innovation which is the power to introduce angklung, accept criticism, and apply parenting. The external business communication strategy consists of joining promotions, becoming a tourist destination, cooperating, strengthening brand associations, flexibly utilizing data, introducing angklung through the internet and conventional, quickly handling complaints, sharing systems that simultaneously strengthen the community economy.